BASIC SCHEME OF EDUCATION ADVOCATED BY MAHATMA GANDHI: THE APOSTLE OF PEACE - Zahida Jan (RADJA PUBLIKA, 2024)
Mahatma Gandhi's Basic Scheme of Education, known as Nai Talim, is a holistic educational philosophy that integrates intellectual, physical, and moral development. Rooted in the socio-economic and cultural context of India, it emphasizes self-sufficiency, practical skills, and the dignity of labor. Central to this approach is the concept of